Electoral turnout and state redistribution: A cross-national study of 14 developed countries - Vincent A. Mahler; David K. Jesuit; Piotr R. Paradowski (Luxembourg Income Study (LIS), 2015)
This study explores the relationship between electoral participation and income redistribution by way of social transfers, using data from the European Social Survey, the Comparative Study of Electoral Systems and the Luxembourg Income Study. It extends previous research by measuring the income skew of turnout rather than using average turnout as a proxy for its income bias. We find that a larger income skew in turnout is negatively related to transfer redistribution and that higher electoral participation by income groups, especially those in the low and middle parts of the income distribution, is associated with greater redistribution in their favor.
Keywords: 330